Baicalein and baicalin as Zika virus inhibitors - Oo, Adrian; Teoh, Boon Teong; Sam, Sing Sin; Bakar, Sazaly Abu; Zandi, Keivan (Archives of virology, 2019)
At present, there is no effective antiviral agent for Zika virus (ZIKV), an arbovirus that is known for its teratogenic effects on newborns. Baicalein and baicalin were found to be capable of downregulating ZIKV replication up to 10 hours postinfection, while prophylactic effects were evident in pre-treated cells. Baicalein exhibited its highest potency during intracellular ZIKV replication, whereas baicalin was most effective against virus entry. Our in silico interaction assays predicted that both compounds exhibited the strongest binding affinities towards ZIKV NS5, while the virus envelope glycoprotein was the least likely target protein. These findings serve as a crucial platform for further in-depth studies to decipher the underlying anti-ZIKV mechanism(s) of each compound.